Отражение женского пола в качестве женщины в русских фразеологических единицах на фоне арабского языка Reflection of Feminine Gender as represented by Women in Russian Idioms in Comparison with Arabic (Journal of the College of Languages (JCL), 2018)
АннотацияВзгляд на пол как на комплексное социальное отношение означает,что роль женщины в истории следует рассматривать не просто как новый для исторической науки предмет исследования, а как обойденный вниманием ученых вопрос об отношениях между людьми или группами людей.Женщина играет особую и важную роль в обществе , даже скажут ,что она половина нашего общества ,поэтому она является второй половиной в месте с мужчиной потому,что она как жена , мать, сестра, дочка, подруга, любовница.каждое из этих названий имеет собственные характеры.В арабском языке как и в русском , есть такие фразеологизмы которые обясняют и важную роль и поведения женщины и даже её место в обществе. Когда мы говорим о мужчине то мужчина всегда герой,самавлюблён ,любопытен , но когда речь идет о женщине в сравнении с мужчиной то можем сказать: мужской ум. об умной женщине . мужик в юбке , женщина ,выполняющая мужскую работу . .Русская фразеология представляет несвободный образ женщины, в зависимости от отношения к муж¬чинам: девушка, невеста , жена ,мать , домохозяйка, старуха, вдова .Abstract Shedding light on the feminine gender as represented by women, as complete social entity, along with the use of idioms referring to women though history should never be seen as a topic of a historical study. It has to be taken into consideration by linguists so as to study it within people in the society. Women play a special role in the community; that they are the other half is never away from the truth. She is a wife, a mother, a sister, a daughter, a girl-friend, and a beloved. All these designations have their own characteristics in Arabic as is the case with Russian. There are idiomatic expressions about women as to their role and status not inferior to men. We try to delimit as many as possible of the idioms used by people in literary writings so as to bring out the importance of this human being. When man is talked about, he is described as brave or as a lover; but when a woman is talked about, she is described differently. She might be described as having a man-mentality, or a man-like role when she is very smart or when she has an important role to play. So, idiomatic expressions may take an ample time and space in linguistic study, especially when she is as a wife or fiancé or mother or house-keeper or a widow.